The Influence of QRIS Payment Customer Satisfaction Towards Customer Loyalty And Continuity - Nadinta, Puti Shalia; Kusumawati, Nurrani (Integrasi Sains Media, 2023)
The official standardized payment system in Indonesia, Quick Response Indonesian Standard (QRIS), was introduced on August 17, 2019. QRIS is anticipated to facilitate QR payment systems, which allow for scanning a single QR code from various digital payment services as long as they are registered with QRIS. The researcher conducted exploratory research to better grasp the consumer perspective on utilizing QRIS due to the increased usage of QRIS over time. It has been discovered that employing QRIS still has its limitations. With that, a more thorough investigation is conducted into the relationship between customer pleasure and loyalty. Perceived Usefulness, Perceived Flow, Satisfaction, Customer Loyalty, and Adoption Continuity are the variables put to the test. The Generation Z population in Indonesia actively utilizing QRIS in the Bandung and Jabodetabek region serves as the study's sample. Data from 205 samples, categorized as Generation Z, were collected and subjected to descriptive and PLS-SEM analyses. According to the study, perceived usefulness and flow favorably affect satisfaction. Also favorably affecting perceived flow is perceived usefulness. Adoption Continuity is positively impacted by satisfaction and perceived utility. Customer loyalty and adoption continuity both benefit from satisfaction. The results of this study are anticipated to have implications for future research as a valuable point of reference for researchers developing new research studies in the field of marketing, as well as for business owners who already offer or will offer QRIS as a payment method to ensure a smooth payment flow for their customers.